Endobronchial Ultrasound An Atlas and Practical Guide - Ernst, Armin; Herth, Felix JF (Springer New York : Imprint: Springer, 2009)
It has been 25 years since the first reports on endoscopic ultrasonography (EUS) began to appear in the medical literature. The technology involves placing an ultrasound transducer at the tip of an endoscope, which allows for ultrasound imaging to be performed from within the gastrointestinal (GI) lumen. It became quickly apparent that for purposes of thoracic applications and cancer staging that smaller and dedicated bronchoscopes for ultrasound imaging and procedure guidance was required and subsequently were developed. Progress in instrumentation design and clinical research continue to expand the potential utility of this still relatively new method. Current indications for EBUS and EUS in oncology can be divided into several main categories: cancer staging; tumor diagnosis and guidance of therapeutic interventions . All the authors of Endobronchial Ultrasound: An Atlas and Practical Guide have helped to establish the field, are well published and have taught multiple courses in bronchoscopy and endobronchial ultrasound for many years, helping to disseminate the prerequisite knowledge in order to properly apply the technology for patients.. Among the topics these experts discuss are: basic principles of TBNA - staging principles in lung cancer - technique and anatomy of radial ultrasound - ultrasound for interventional procedures - ultrasound for peripheral lesions - EBUS TBNA bronchoscopy - ultrasound as a therapeutic instrument Endobronchial ultrasound has received explosive attention amongst pulmonologists, thoracic surgeons and gastroenterologists over the past few years and technical modifications continue to lead to the potential for ubiquitious use.